1992
DOI: 10.1038/jcbfm.1992.120
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Profound Levels of Hypothermia (Below 14°C) on Canine Cerebral Metabolism

Abstract: Summary: The goal of this study was to determine the temperature coefficient (QIO) for canine CMR02 at tem peratures below 14°C. Eight dogs were anesthetized with halothane for surgical preparation. The animals were placed on total cardiopulmonary bypass and CBF was measured by direct sagittal sinus outflow. Duplicate mea surements were taken at 37, 13, and 7°C. The EEG be came isoelectric at a temperature of 12.0 ± 0.8°C. The QIO between 13 and 7°C was 2.19 ± 0.59. With rewarming to 37°C, cerebral metabolic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 13 publications
2
30
0
1
Order By: Relevance
“…At deeper hypothermic temperatures (4°C), extensive damage was seen after 8 hours. It is unsurprising that such deep temperatures would cause damage so quickly; Michenfelder noted changes in electrical activity in canines starting at 27°C, with loss of signal occurring at *12°C (Michenfelder and Milde, 1992). This is a new finding for moderate and profound hypothermia and is consistent with our previously published work identifying neuron-specific injury after ultra-profound hypothermia, involving cooling and rewarming to 4°C .…”
Section: Hypothermia By Itself With No Additional Insult Can Cause Insupporting
confidence: 80%
“…At deeper hypothermic temperatures (4°C), extensive damage was seen after 8 hours. It is unsurprising that such deep temperatures would cause damage so quickly; Michenfelder noted changes in electrical activity in canines starting at 27°C, with loss of signal occurring at *12°C (Michenfelder and Milde, 1992). This is a new finding for moderate and profound hypothermia and is consistent with our previously published work identifying neuron-specific injury after ultra-profound hypothermia, involving cooling and rewarming to 4°C .…”
Section: Hypothermia By Itself With No Additional Insult Can Cause Insupporting
confidence: 80%
“…Our experimental model was designed to mimic the presence of complete cardiopulmonary failure as the worst possible case for the application of ECLS. In the literature only few experimental investigations have been reported that describe the effects of total bypass ECLS on cerebral metabolism and electrophysiology, which reflects the difficulty of establishing total bypass in small animals [17,18]. Our study of 2 h normothermic ECLS in cats revealed that brain tissues and plasma lactate substantially increased although blood pressure was maintained close to normal.…”
Section: Discussionmentioning
confidence: 70%
“…The first assumes that ischemic injury occurs secondary to depletion of metabolic stores and that hypothermia preserves these stores by reducing cerebral metabolic rate of oxygen consumption (CMRO 2 ). In animal models of cerebral ischemia, CMRO 2 declines monotonically by ϳ4.5% per degree over the range of 37-38°C (normothermia) to 15-18°C (profound hypothermia) (Michenfelder and Milde, 1992). These findings are clinically relevant, because recovery of normal function in humans can be observed after 60 min of circulatory arrest when the arrest occurs at 15-18°C (Tharion et al, 1982).…”
mentioning
confidence: 66%